The Longitudinal Association Between Cardiovascular Risk and Cognitive Function in Middle-Aged and Older Adults in China: A Nationally Representative Cohort Study - Hua, Wei; Hou, Jianhua; Jiang, Taiyi; Su, Bin; Fu, Jiangning; Sun, Runsong; Chang, Biru; Xia, Wei; Wu, Hao; Zhang, Tong; Guo, Caiping; Wang, Wen (Frontiers in Cardiovascular Medicine, 2020)
Abstract Objective China has the largest population living with dementia, causing a tremendous burden on the aging society. Cardiovascular disease (CVD) may trigger a cascade of pathologies associated with cognitive aging. We aim to investigate the association between cardiovascular risk (CVR) factors and cognitive function in the nationally representative cohort in China. Methods Participants were recruited from 150 counties in 28 provinces via a four-stage sampling method. The outcomes included several cognitive tasks. The independent variable was a composite score of cardiovascular risk calculated from sex-specific equations. We fitted the time-lagged regression to model the association between CVR and cognition. Besides, we performed cross-group analyses to test for model invariance across sex and age. We thus constrained path coefficients to be equal across each grouping variable (e.g., sex) and compared the fit of this constrained model with an unconstrained model in which the path coefficients were allowed to vary by group. Results A total of 3799 participants were included in the final analyses. We found that the CVR had a negative linear association with global cognition (β=-0.1, p<0.01). Additionally, CVR had inverse linear associations with domain-specific measurements of memory and learning, calculation, orientation, and visual-spatial ability (all ps<0.01). Regarding sex and age moderation, Males had a more pronounced association between higher CVR and worse general cognition, immediate recall, orientation, the calculation, and visual-spatial ability (all ps<0.0001). In contrast, females exhibited a slightly larger negative association in delayed recall. Older participants (>65 years old) had a more pronounced association between higher CVR and worse calculation ability (p=0.003). Conclusion CVD are risk factors for lower global cognition and cognitive sub-domains in middle-aged and older adults in China.